In vitro evaluation of fungicides and plant extracts against the fungi associated with seeds of nine chickpea varieties - Khatun, Amina; Shamsi, Shamim (Dhaka University Journal of Biological Sciences, 2016)
A total of nine species of fungi were found to be associated with seeds of nine varieties of chickpea. The isolated fungi were Alternaria alternata (Fr.) Keissler, Aspergillus flavus Link., A. niger Van Tiegh., A. fumigatus Fresenius., A. nidulans Eidam, Curvularia lunata (Wakker) Boedijn, Penicillium Link., Rhizopus stolonifer (Ehrenb.: Fr.) Vuill and Trichoderma viride Pers. Five fungicides viz., Bavistin 50 WP, Dithane M-45, Greengel 72 WP, Ridomil MZ Gold and Tall 25 EC at 100, 200, 300, 400 and 500 ppm were evaluated against the test fungi. Tall 25 EC were found most efficient inhibitor which completely inhibited the radial growth of the test fungi followed by Bavistin 50 WP, Dithane M-45 and Greengel 72 WP. Antifungal properties of ethanol extracts of Azadirachta indica A. Juss., Allium sativum L., Citrus medica L., Datura metel L. and Psidium guajava L. at 5, 10 and 20% concentrations were evaluated against the test fungi. Allium sativum L. was found most efficient inhibitor of the test fungi followed by D. metel L., A. indica A. Juss., C. medica L. and P. guajava L. Dhaka Univ. J. Biol. Sci. 25(1): 83-90, 2016